Production process of cubic boron nitride cutter

By pretreating, cleaning, activating, depositing TiB2 coating, and annealing the cubic boron nitride preform, the problem of poor coating adhesion in cubic boron nitride cutting tools was solved, thereby improving the overall performance and service life of the tools.

CN119504266APending Publication Date: 2025-02-25KUNSHAN TESHENGLONG PRECISION TOOLS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411693465.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Poor adhesion between cubic boron nitride cutting tools and coatings leads to easy detachment of the coating material, affecting tool performance and service life.

Method used

After pretreatment, cleaning, and activation of the cubic boron nitride preform, a TiB2 coating is deposited on its surface and then annealed to form a strong metallurgical bond.

Benefits of technology

It improves the adhesion between the coating and the blank, enhances the hardness and wear resistance of the tool, extends its service life, and improves cutting efficiency and machining accuracy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005151561650000101
    Figure BDA0005151561650000101
  • Figure BDA0005151561650000111
    Figure BDA0005151561650000111
Patent Text Reader

Abstract

The invention relates to the technical field of cutter machining, and discloses a cubic boron nitride cutter production process, which comprises the following steps of: mixing and sintering cubic boron nitride powder, tungsten carbide powder and TiCN serving as raw materials to obtain a cubic boron nitride blank, treating the surface, and polishing by different diamond grinding wheels to remove impurities and defects on the surface of the blank, thereby obtaining the cubic boron nitride cutter. The preparation method comprises the following steps: carrying out surface cleaning and activation treatment on a cubic boron nitride blank to improve the surface cleanliness of the blank and obtain a pretreated cubic boron nitride blank, carrying out surface cleaning and activation treatment to improve the surface activity and wettability of the blank, greatly improving the binding force between a coating and the blank, and carrying out Ti B2 coating deposition on the surface, so that excellent adhesiveness, compactness, smoothness, hardness and coating toughness are achieved; and through annealing treatment, combination between the coating and the blank is promoted, it is guaranteed that the coating is not prone to falling off or peeling off in the use process of the tool, and therefore the comprehensive performance of the tool is improved, and the service life of the tool is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of tool processing, in particular to a production process of a cubic boron nitride tool. Background Art

[0002] Cubic boron nitride (CBN) is a superhard material with excellent hardness, wear resistance, chemical stability and thermal stability. It is often used to manufacture cutting tools for cutting high-hardness and difficult-to-process materials. Its thermal stability is much higher than that of diamond. When processing materials containing iron-based metal elements, it has obvious advantages over diamond materials. Therefore, it is often used to process ferrous metals and has a wide range of applications in the cutting of high-hardness metal materials such as cast iron, high-speed steel and hardened steel. Among them, cubic boron nitride coated tools use cubic boron nitride as the matrix, and the current manufacturing of cubic boron nitride tools mainly uses polycrystalline cubic boron nitride (PCBN) as the matrix to form a cemented carbide coating on the surface of the tool. The coating on the tool can effectively reduce tool wear, greatly improve tool life, cutting efficiency and processing accuracy, and reduce tool costs and consumption costs, and can be used in the field of mechanical technicians with higher requirements.

[0003] At present, cubic boron nitride coated tools mainly use the physical vapor deposition method to deposit titanium-based carbide coatings on cubic boron nitride substrates. The main problem is that the bonding between the coating and the tool substrate is not strong, which causes the coating material to fall off, resulting in poor overall tool performance during cutting. TiB2 is a superhard tool coating material developed in recent years. It has properties such as high hardness, high melting point, and good oxidation resistance. It also has a relatively low chemical affinity with non-ferrous metals and has broad application prospects in the processing of non-ferrous metals such as aluminum alloys and titanium alloys. However, during the use of TiB2 coatings, there is also the problem of poor bonding with the substrate, showing the characteristic of easy fragmentation, which limits its application in cubic boron nitride tools. Summary of the invention

[0004] 1. Technical issues to be resolved

[0005] In view of the deficiencies in the prior art, the present invention provides a production process for cubic boron nitride cutting tools, which solves the problem of poor bonding between cubic boron nitride cutting tools and coatings and increases the service life of the cutting tools.

[0006] (II) Technical solution

[0007] In order to achieve the above object, the present invention discloses a cubic boron nitride tool production process, comprising the following steps:

[0008] S1. Pre-treating the cubic boron nitride embryo by rough grinding, fine grinding and grinding to obtain a pre-treated cubic boron nitride embryo;

[0009] S2, cleaning the surface of the cubic boron nitride embryo body pretreated in S1, drying at 60° C. for 6 h, heating, vacuumizing, and then activating the surface to obtain an activated cubic boron nitride embryo body;

[0010] S3, depositing a coating on the surface of the cubic boron nitride embryo after activation in S2, forming a coating on the surface of the cubic boron nitride embryo, and obtaining a coated cubic boron nitride embryo;

[0011] S4. Annealing the coated cubic boron nitride embryo to obtain a cubic boron nitride tool.

[0012] Preferably, the cubic boron nitride embryo in S1 is obtained by mixing and sintering cubic boron nitride powder, tungsten carbide powder and TiCN in a mass ratio of 95:2:3.

[0013] Preferably, the sintering process in S1 is as follows: cubic boron nitride powder, tungsten carbide powder and TiCN are mixed, placed in a graphite mold, pre-pressed axially at a pressure of 45 MPa, and sintered. During the sintering process, pressurization is performed, the pressure is 105 MPa, the sintering temperature is 1600-1800°C, the sintering time is 12-15 min, and then the incision process is performed to obtain a cubic boron nitride embryo.

[0014] Preferably, the specific steps of pretreatment of the S1 neutral cubic boron nitride embryo for rough grinding, fine grinding and grinding include the following steps: during the rough grinding process, a 180-240 resin bond diamond grinding wheel is used, and the feed amount is 0.01mm / double stroke; during the fine grinding process, a Wl0-W14 resin bond grinding wheel is used, and the feed amount is 0.005mm / double stroke; during the grinding process, a W3-W5 diamond grinding wheel is used.

[0015] Preferably, the cleaning step in S2 is specifically as follows: ultrasonically cleaning the pretreated cubic boron nitride embryo in acetone and anhydrous ethanol for 15-30 minutes in sequence, and then washing with deionized water.

[0016] Preferably, the temperature in S2 is heated to 300-320°C, kept warm for 25-35 minutes, and the vacuum degree of the vacuum is 7.5×10 - 3 Pa, the vacuum treatment time is 60-90min.

[0017] Preferably, the activation treatment in S2 adopts a plasma etching method. During the plasma etching process, the temperature of the embryo surface is 520-550° C., the flow rate of argon gas is 850-950 sccm, the voltage of the ion source is 45-55V, and the treatment time is 45-60 min.

[0018] Preferably, the specific process of depositing the coating in S3 is as follows: the vacuum degree of the reaction chamber is 10 -4 Under the vacuum condition of 1.5477 W / m, TIB2 was used as the target material for vacuum magnetron sputtering coating. TIB2 was deposited on the embryo body at an ion deposition rate of 15 nm / min to form a coating with a thickness of 0.2-0.5 μm.

[0019] Preferably, the power of the magnetron sputtering is 2-6 kW, the frequency is 500-800 Hz, the pulse ratio is 2-8%, and the bias voltage is -40V to -100V.

[0020] Preferably, the temperature of the annealing treatment in S4 is 800-900° C., and the time of the annealing treatment is 1-2 hours.

[0021] (III) Beneficial technical effects

[0022] In the present invention, cubic boron nitride powder, tungsten carbide powder and TiCN are used as raw materials, and a cubic boron nitride embryo is obtained by mixed sintering. The surface of the cubic boron nitride embryo is treated, and different diamond grinding wheels are used to grind to obtain a pretreated cubic boron nitride embryo. After the surface of the pretreated cubic boron nitride embryo is cleaned and activated, a TI B2 coating is deposited on the surface, and after annealing, a cubic boron nitride tool is obtained.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The cubic boron nitride tool used in the present invention has excellent wear resistance, high hardness, can maintain a sharp cutting edge for a long time, reduce the frequency of tool replacement, improve production efficiency, and effectively improve the grinding quality and surface integrity of the workpiece. Cubic boron nitride has high thermal stability, can still maintain stable cutting performance at high temperatures, is not prone to thermal deformation or oxidation, is suitable for processing difficult-to-process materials such as high-temperature alloys, and has greater chemical stability to iron-based metal elements. It is not easy to react chemically with the workpiece material during the processing, thereby ensuring the durability and processing accuracy of the tool.

[0025] (2) In the present invention, the impurities and defects on the surface of the embryo are removed through the steps of rough grinding, fine grinding and grinding, and the cleanliness of the surface of the embryo is improved, which lays the foundation for the subsequent coating deposition and the improvement of tool performance. Cleaning the surface of the embryo can effectively remove the oil and adsorbents on the surface of the embryo, so that the coating can be evenly and firmly attached to the surface of the embryo. Heating treatment can increase the temperature of the embryo and further remove moisture and volatile substances in the embryo. Vacuuming can remove the gas and impurities around the embryo, creating a clean, oxygen-free environment for subsequent activation treatment. Activating the surface of the embryo can improve the activity and wettability of the embryo surface and greatly improve the bonding force between the coating and the embryo. The TIB2 coating is deposited on the embryo and has excellent adhesion, density, smoothness, hardness and coating toughness. After the coating is deposited, it is annealed to help eliminate stress and defects inside the coating and improve the stability and durability of the coating. Furthermore, the annealing treatment can also promote the bonding between the coating and the blank, ensuring that the coating is not prone to falling off or peeling off during the use of the tool, thereby improving the comprehensive performance and service life of the tool.

[0026] (3) In the present invention, a TIB2 coating is formed on the embryo, and a good metallurgical bond can be formed between the TIB2 coating and the embryo. During the deposition process, the sputtered atoms or molecules will chemically bond with the atoms on the surface of the tool embryo, significantly improving the hardness and wear resistance of the cubic boron nitride tool, thereby extending the service life and chemical stability of the tool. The tool after sputtering deposition can better resist the erosion of harsh environments such as high temperature, high pressure, strong acid and strong alkali during the cutting process, reduce the friction coefficient and cutting temperature, thereby improving the cutting efficiency and processing quality, and avoiding the occurrence of bonding during the cutting process. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0028] Example 1

[0029] A cubic boron nitride tool production process comprises the following steps:

[0030] S1. Mix cubic boron nitride powder, tungsten carbide powder and TiCN in a mass ratio of 95:2:3, place in a graphite mold, pre-press in the axial direction at a pressure of 45 MPa, and sinter. During the sintering process, pressurize at a pressure of 105 MPa, sinter at a temperature of 1600°C, and sinter for 15 min. Then perform incision processing to obtain a cubic boron nitride embryo. The cubic boron nitride embryo is pretreated by rough grinding, fine grinding, and grinding. During the rough grinding process, a No. 180 resin bond diamond grinding wheel is used, and the feed amount is 0.01 mm / double stroke; during the fine grinding process, a W10 resin bond grinding wheel is used, and the feed amount is 0.005 mm / double stroke; during the grinding process, a W3 diamond grinding wheel is used to obtain the pretreated cubic boron nitride embryo;

[0031] S2. Clean the surface of the pretreated cubic boron nitride embryo, and then use acetone and anhydrous ethanol ultrasonic cleaning for 15 minutes, and then wash with deionized water. After cleaning, dry at 60 ° C for 6 hours, heat to 300 ° C, keep warm for 35 minutes, and evacuate. The vacuum degree of evacuation is 7.5×10 -3 Pa, vacuum treatment time is 60min, and then activation treatment is performed. The activation treatment adopts a plasma etching method. During the plasma etching process, the temperature of the embryo surface is 520°C, the flow rate of argon gas is 850sccm, the voltage of the ion source is 45V, and the treatment time is 60min to obtain an activated cubic boron nitride embryo;

[0032] S3, depositing a coating on the surface of the activated cubic boron nitride embryo. During the coating deposition process, the vacuum degree of the reaction chamber is 10 -4 Under the vacuum condition of 1.5 Pa, TIB2 is used as a target material for vacuum magnetron sputtering coating, the power of magnetron sputtering is 2 kW, the frequency is 500 Hz, the pulse ratio is 2%, the bias voltage is -40 V, TIB2 is deposited on the embryo, the ion deposition rate is 15 nm / min, a coating is formed, the thickness of the coating is 0.2 μm, and a coating is formed on the surface of the cubic boron nitride embryo to obtain a coated cubic boron nitride embryo;

[0033] S4. Annealing the coated cubic boron nitride embryo at a temperature of 800° C. for 2 h to obtain a cubic boron nitride tool.

[0034] Example 2

[0035] A cubic boron nitride tool production process comprises the following steps:

[0036] S1. Mix cubic boron nitride powder, tungsten carbide powder and TiCN in a mass ratio of 95:2:3, place in a graphite mold, pre-press in the axial direction at a pressure of 45 MPa, and sinter. During the sintering process, pressurize at a pressure of 105 MPa, sinter at a temperature of 1700°C, and sinter for 14 min, and then perform incision processing to obtain a cubic boron nitride embryo. The cubic boron nitride embryo is pretreated by rough grinding, fine grinding, and grinding. During the rough grinding process, a No. 210 resin bond diamond grinding wheel is used, and the feed amount is 0.01 mm / double stroke; during the fine grinding process, a W12 resin bond grinding wheel is used, and the feed amount is 0.005 mm / double stroke; during the grinding process, a W4 diamond grinding wheel is used to obtain the pretreated cubic boron nitride embryo;

[0037] S2. Clean the surface of the pretreated cubic boron nitride embryo, and then use acetone and anhydrous ethanol ultrasonic cleaning for 18 minutes, and then wash with deionized water. After cleaning, dry at 60 ° C for 6 hours, heat to 305 ° C, keep warm for 30 minutes, and evacuate. The vacuum degree of evacuation is 7.5×10 -3 Pa, vacuum treatment time is 70min, and then activation treatment is performed. The activation treatment adopts a plasma etching method. During the plasma etching process, the temperature of the embryo surface is 530°C, the flow rate of argon gas is 880sccm, the voltage of the ion source is 48V, and the treatment time is 50min to obtain an activated cubic boron nitride embryo;

[0038] S3, depositing a coating on the surface of the activated cubic boron nitride embryo. During the coating deposition process, the vacuum degree of the reaction chamber is 10 -4 Under the vacuum condition of 1.577 Pa, TIB2 is used as the target material for vacuum magnetron sputtering coating. The power of magnetron sputtering is 4 kW, the frequency is 600 Hz, the pulse ratio is 4%, the bias voltage is -60 V, TIB2 is deposited on the embryo, the ion deposition rate is 15 nm / min, and a coating is formed. The thickness of the coating is 0.4 μm, and a coating is formed on the surface of the cubic boron nitride embryo to obtain a coated cubic boron nitride embryo.

[0039] S4. Annealing the coated cubic boron nitride embryo at a temperature of 820° C. for 1.5 h to obtain a cubic boron nitride tool.

[0040] Example 3

[0041] A cubic boron nitride tool production process comprises the following steps:

[0042] S1. Clean the surface of the pretreated cubic boron nitride embryo, and then use acetone and anhydrous ethanol ultrasonic cleaning for 25 minutes, and then use deionized water to wash. After cleaning, dry at 60 ° C for 6 hours, heat to 315 ° C, keep warm for 30 minutes, and evacuate. The vacuum degree of evacuation is 7.5×10 -3 Pa, vacuum treatment time is 80min, and then activation treatment is performed. The activation treatment adopts the method of plasma etching. During the plasma etching process, the temperature of the embryo surface is 540°C, the flow rate of argon gas is 920sccm, the voltage of the ion source is 50V, and the treatment time is 55min to obtain an activated cubic boron nitride embryo;

[0043] S2, depositing a coating on the surface of the activated cubic boron nitride embryo. During the coating deposition process, the vacuum degree of the reaction chamber is 10 -4 Under the vacuum condition of 1.577 Pa, TIB2 is used as a target material for vacuum magnetron sputtering coating. The power of magnetron sputtering is 5 kW, the frequency is 700 Hz, the pulse ratio is 5%, the bias voltage is -80 V, TIB2 is deposited on the embryo, the ion deposition rate is 15 nm / min, and a coating is formed. The thickness of the coating is 0.4 μm, and a coating is formed on the surface of the cubic boron nitride embryo to obtain a coated cubic boron nitride embryo.

[0044] S3. Annealing the coated cubic boron nitride embryo at a temperature of 850° C. for 1.5 h to obtain a cubic boron nitride tool.

[0045] The method for preparing the pretreated cubic boron nitride embryo is the same as the method for preparing the pretreated cubic boron nitride embryo in Example 2.

[0046] Example 4

[0047] A cubic boron nitride tool production process comprises the following steps:

[0048] S1. Mix cubic boron nitride powder, tungsten carbide powder and TiCN in a mass ratio of 95:2:3, place in a graphite mold, pre-press in the axial direction at a pressure of 45 MPa, and sinter. During the sintering process, pressurize at a pressure of 105 MPa, sinter at a temperature of 1800°C, and sinter for 12 min. Then perform incision processing to obtain a cubic boron nitride embryo. The cubic boron nitride embryo is pretreated by rough grinding, fine grinding, and grinding. During the rough grinding process, a No. 240 resin bond diamond grinding wheel is used, and the feed amount is 0.01 mm / double stroke; during the fine grinding process, a W14 resin bond grinding wheel is used, and the feed amount is 0.005 mm / double stroke; during the grinding process, a W5 diamond grinding wheel is used to obtain the pretreated cubic boron nitride embryo;

[0049] S2. Clean the surface of the pretreated cubic boron nitride embryo, and then use acetone and anhydrous ethanol ultrasonic cleaning for 30 minutes, and then wash with deionized water. After cleaning, dry at 60 ° C for 6 hours, heat to 320 ° C, keep warm for 25 minutes, and evacuate. The vacuum degree of evacuation is 7.5×10 -3 Pa, vacuum treatment time is 90min, and then activation treatment is performed. The activation treatment adopts the method of plasma etching. During the plasma etching process, the temperature of the embryo surface is 550°C, the flow rate of argon gas is 950sccm, the voltage of the ion source is 55V, and the treatment time is 45min to obtain an activated cubic boron nitride embryo;

[0050] S3, depositing a coating on the surface of the activated cubic boron nitride embryo. During the coating deposition process, the vacuum degree of the reaction chamber is 10 -4 Under the vacuum condition of 1.5 Pa, using TB2 as the target material, vacuum magnetron sputtering coating is carried out, the power of magnetron sputtering is 6 kW, the frequency is 800 Hz, the pulse ratio is 8%, the bias voltage is -100 V, TB2 is deposited on the embryo, the ion deposition rate is 15 nm / min, and a coating is formed. The thickness of the coating is 0.5 μm, and a coating is formed on the surface of the cubic boron nitride embryo to obtain a coated cubic boron nitride embryo;

[0051] S4. Annealing the coated cubic boron nitride embryo at a temperature of 900° C. for 1 h to obtain a cubic boron nitride tool.

[0052] Comparative Example 1

[0053] A cubic boron nitride tool production process comprises the following steps:

[0054] S1. Mix cubic boron nitride powder, tungsten carbide powder and TiCN in a mass ratio of 95:2:3, place in a graphite mold, pre-press in the axial direction at a pressure of 45 MPa, and sinter. During the sintering process, pressurize at a pressure of 105 MPa, sinter at a temperature of 1700°C, and sinter for 14 min, and then perform incision processing to obtain a cubic boron nitride embryo;

[0055] S2. The surface of the cubic boron nitride embryo was cleaned by ultrasonic cleaning with acetone and anhydrous ethanol for 25 minutes, and then washed with deionized water. After cleaning, it was dried at 60°C for 6 hours, heated to 315°C, kept warm for 30 minutes, and evacuated to a vacuum degree of 7.5×10 -3Pa, vacuum treatment time is 80min, and then activation treatment is performed. The activation treatment adopts the method of plasma etching. During the plasma etching process, the temperature of the embryo surface is 540°C, the flow rate of argon gas is 920sccm, the voltage of the ion source is 50V, and the treatment time is 55min to obtain an activated cubic boron nitride embryo;

[0056] S3, depositing a coating on the surface of the activated cubic boron nitride embryo. During the coating deposition process, the vacuum degree of the reaction chamber is 10 -4 Under the vacuum condition of 1.577 Pa, TIB2 is used as a target material for vacuum magnetron sputtering coating. The power of magnetron sputtering is 5 kW, the frequency is 700 Hz, the pulse ratio is 5%, the bias voltage is -80 V, TIB2 is deposited on the embryo, the ion deposition rate is 15 nm / min, and a coating is formed. The thickness of the coating is 0.4 μm, and a coating is formed on the surface of the cubic boron nitride embryo to obtain a coated cubic boron nitride embryo.

[0057] S4. Annealing the coated cubic boron nitride embryo at a temperature of 850° C. for 1.5 h to obtain a cubic boron nitride tool.

[0058] Comparative Example 2

[0059] A cubic boron nitride tool production process comprises the following steps:

[0060] S1. Mix cubic boron nitride powder, tungsten carbide powder and TiCN in a mass ratio of 95:2:3, place in a graphite mold, pre-press in the axial direction at a pressure of 45 MPa, and sinter. During the sintering process, pressurize at a pressure of 105 MPa, sinter at a temperature of 1700°C, and sinter for 14 min, and then perform incision processing to obtain a cubic boron nitride embryo. The cubic boron nitride embryo is pretreated by rough grinding, fine grinding, and grinding. During the rough grinding process, a No. 210 resin bond diamond grinding wheel is used, and the feed amount is 0.01 mm / double stroke; during the fine grinding process, a W12 resin bond grinding wheel is used, and the feed amount is 0.005 mm / double stroke; during the grinding process, a W4 diamond grinding wheel is used to obtain the pretreated cubic boron nitride embryo;

[0061] S2. Clean the surface of the pretreated cubic boron nitride embryo, and then use acetone and anhydrous ethanol ultrasonic cleaning for 25 minutes, and then wash with deionized water. After cleaning, dry at 60 ° C for 6 hours, heat to 315 ° C, keep warm for 30 minutes, and evacuate. The vacuum degree of evacuation is 7.5×10 -3Pa, vacuum treatment time is 80min, and then activation treatment is performed. The activation treatment adopts the method of plasma etching. During the plasma etching process, the temperature of the embryo surface is 540°C, the flow rate of argon gas is 920sccm, the voltage of the ion source is 50V, and the treatment time is 55min to obtain an activated cubic boron nitride embryo;

[0062] S3. Annealing the activated cubic boron nitride embryo at a temperature of 850° C. for 1.5 h to obtain a cubic boron nitride tool.

[0063] Comparative Example 3

[0064] A cubic boron nitride tool production process comprises the following steps:

[0065] S1. Mix cubic boron nitride powder, tungsten carbide powder and TiCN in a mass ratio of 95:2:3, place in a graphite mold, pre-press in the axial direction at a pressure of 45 MPa, and sinter. During the sintering process, pressurize at a pressure of 105 MPa, sinter at a temperature of 1700°C, and sinter for 14 min, and then perform incision processing to obtain a cubic boron nitride embryo;

[0066] S2. The surface of the cubic boron nitride embryo was cleaned by ultrasonic cleaning with acetone and anhydrous ethanol for 25 minutes, and then washed with deionized water. After cleaning, it was dried at 60°C for 6 hours, heated to 315°C, kept warm for 30 minutes, and evacuated to a vacuum degree of 7.5×10 -3 Pa, vacuum treatment time is 80min, and then activation treatment is performed. The activation treatment adopts the method of plasma etching. During the plasma etching process, the temperature of the embryo surface is 540°C, the flow rate of argon gas is 920sccm, the voltage of the ion source is 50V, and the treatment time is 55min to obtain an activated cubic boron nitride embryo;

[0067] S3. Annealing the activated cubic boron nitride embryo at a temperature of 850° C. for 1.5 h to obtain a cubic boron nitride tool.

[0068] The particle size of the cubic boron nitride powder used in the examples and comparative examples of the present invention is 1-3 μm, and the purity is 99.9%; the particle size of the tungsten carbide powder is 500 nm, and the purity is 99.9%; the particle size of TiCN is 1-2 μm, and the purity is 99.9%; other undisclosed reagents are all commercially available.

[0069] The performance of the cubic boron nitride cutting tools prepared in Examples 1-4 and Comparative Examples 1-3 was tested:

[0070] (1) Hardness test: The microhardness of the sintered sample was measured using a TH-700 Vickers hardness tester with a load of 9.8 N and a holding time of 15 s.

[0071] (2) Bending strength test: The bending test was carried out on an AG-IC-50KN multifunctional mechanical testing machine using the three-point bending method, with a pressing speed of 0.5 mm / min. -1 ;

[0072] (3) Adhesion strength: Adhesion scratch test was performed using a conical diamond indenter with a cone angle of 120° and a tip radius of 0.2 mm. A positive pressure of 80 N was applied continuously at a speed of 80 N / min and the indenter slid on the coating surface at a speed of 4 mm / min to detect the film / substrate bonding strength.

[0073] (4) Coated tool cutting test: The cut material was PCrNi3MoVA steel. The flank wear was observed and measured using a 30x tool microscope. The cutting time when the width of the blade wear band was greater than 0.6 mm was used as the tool life assessment standard to compare the tool cutting life.

[0074] The above test results are shown in Table 1:

[0075] Table 1

[0076]

[0077]

[0078] According to the test results in Table 1, it can be seen that the cubic boron nitride cutting tools corresponding to Examples 1-4 have excellent comprehensive performance, excellent hardness, mechanical properties, good coating adhesion strength, and long cutting life. In Comparative Example 1, the embryo body was not polished, which had a certain impact on the comprehensive performance and deteriorated the comprehensive performance. In Comparative Example 2, no coating was deposited on the embryo body surface, the hardness was greatly reduced, and the cutting life was shortened.

[0079] Although the embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that all equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.

Claims

1. A cubic boron nitride tool production process, characterized in that: The steps include: S1. Pre-treating the cubic boron nitride embryo by rough grinding, fine grinding and grinding to obtain a pre-treated cubic boron nitride embryo; S2, cleaning the surface of the cubic boron nitride embryo body pretreated in S1, drying, heating, vacuuming, and then activating the surface to obtain an activated cubic boron nitride embryo body; S3, depositing a coating on the surface of the cubic boron nitride embryo after activation in S2, forming a coating on the surface of the cubic boron nitride embryo, and obtaining a coated cubic boron nitride embryo; S4. Annealing the coated cubic boron nitride embryo to obtain a cubic boron nitride tool.

2. A cubic boron nitride tool production process according to claim 1, characterized in that: The cubic boron nitride embryo in S1 is obtained by mixing and sintering cubic boron nitride powder, tungsten carbide powder and TiCN in a mass ratio of 95:2:

3.

3. A cubic boron nitride tool production process according to claim 2, characterized in that: The sintering process in S1 is as follows: cubic boron nitride powder, tungsten carbide powder and TiCN are mixed, placed in a graphite mold, pre-pressed in the axial direction at a pressure of 45MPa, and sintered. During the sintering process, pressurization is performed, the pressure is 105MPa, the sintering temperature is 1600-1800°C, the sintering time is 12-15min, and then the incision process is performed to obtain a cubic boron nitride embryo.

4. The process for producing a cubic boron nitride tool according to claim 1, characterized in that: The specific steps of pretreatment of the S1 neutral cubic boron nitride embryo for rough grinding, fine grinding and grinding include the following steps: during the rough grinding process, a 180-240 resin bond diamond grinding wheel is used, and the feed amount is 0.01mm / double stroke; during the fine grinding process, a Wl0-W14 resin bond grinding wheel is used, and the feed amount is 0.005mm / double stroke; during the grinding process, a W3-W5 diamond grinding wheel is used.

5. The process for producing a cubic boron nitride tool according to claim 1, characterized in that: The cleaning step in S2 is specifically as follows: the pretreated cubic boron nitride embryo is ultrasonically cleaned with acetone and anhydrous ethanol for 15-30 minutes in sequence, and then washed with deionized water.

6. The process for producing a cubic boron nitride tool according to claim 1, characterized in that: The S2 is heated to 300-320°C, kept warm for 25-35 minutes, and the vacuum degree of the vacuum is 7.5×10 -3 Pa, the vacuum treatment time is 60-90min.

7. The process for producing a cubic boron nitride tool according to claim 1, characterized in that: The activation treatment in S2 adopts a plasma etching method. During the plasma etching process, the temperature of the embryo surface is 520-550° C., the flow rate of argon gas is 850-950 sccm, the voltage of the ion source is 45-55V, and the treatment time is 45-60 minutes.

8. The process for producing a cubic boron nitride tool according to claim 1, characterized in that: The specific process of depositing the coating in S3 is as follows: the vacuum degree of the reaction chamber is 10 -4 Under the vacuum condition of 1.5477 W / m, TIB2 was used as the target material for vacuum magnetron sputtering coating. TIB2 was deposited on the embryo body at an ion deposition rate of 15 nm / min to form a coating with a thickness of 0.2-0.5 μm.

9. A cubic boron nitride tool production process according to claim 8, characterized in that: The power of the magnetron sputtering is 2-6kW, the frequency is 500-800Hz, the pulse ratio is 2-8%, and the bias voltage is -40V to -100V.

10. The process for producing a cubic boron nitride tool according to claim 1, characterized in that: The temperature of the annealing treatment in S4 is 800-900° C., and the time of the annealing treatment is 1-2 hours.